Gangrenous cholecystitis during extracorporeal membrane oxygenation operation: A case report and literature review - Wu, Peipei; Wang, Shuai; Gu, Qiao; Zhu, Ying; Hu, Wei; Liu, Bingwei (Frontiers in Medicine, 2023)
A 50-year-old male presented to the emergency department of a hospital with an acute myocardial infarction who underwent cardiopulmonary resuscitation (CPR) followed by extracorporeal membrane oxygenation (ECMO). The patient had persistent jaundice during the course of the disease, the cause of which was never identified, and was later found to be gangrenous cholecystitis after a dissection. We believe this case report will alert clinicians to the possibility of this complication and encourage early detection and intervention to improve the prognosis. Traditionally, the gallbladder has received secondary attention in patients receiving ECMO support, as vital organs tend to be prioritized. However, this case report illustrates the importance of preserving gallbladder function in patients receiving ECMO support.